Pulmonary thromboendarterectomy in the setting of a mediastinal venous malformation with a congenitally absent left subclavian vein. (1st February 2017) - Tejwani, Vickram; Karuppasamy, Karunakaravel; Gomes, Marcelo P.; Levitin, Abraham; Luethke, James M.; Morin, Christopher J.; Smedira, Nicholas G.; Heresi, Gustavo A.; Yakes, Wayne F.
Abstract : Venous malformations have static venous lakes that predispose to spontaneous venous thrombosis within the malformation due to its low‐flow static state. Thrombi of varying sizes can then embolize continually into the pulmonary arterial circulation, and occlude and narrow elastic pulmonary arteries causing chronic thromboembolic pulmonary hypertension (CTEPH). Pulmonary thromboendarterectomy (PTE) is potentially curative in CTEPH, but has not been previously reported in the setting of mediastinal and chest wall venous malformations. We report the case of a 21‐year‐old female with such a large malformation treated successfully with PTE. The patient underwent complete endovascular reconstruction of her subclavian vein system from the axillary vein to the innominate vein stump with covered stent grafts to exclude the malformations from causing recurrent pulmonary emboli. This was followed by embolization of the malformation to allow for the surgical approach. The series of events in this case serves as a novel approach in managing such rare patients.